EFFECTS OF PSYCHOLOGICAL OWNERSHIP MANAGER ON JOB SATISFACTION AND ENTERPRENEUR BEHAVIOR - Prasetyo, Budi; Napitupulu, Lucia (International Journal of Research -GRANTHAALAYAH, 2019)
Managerial entrepreneurial behavior is very important for corporate entrepreneurship, and there is still little research on anticeden and its determinants. Knowledge of the role of psychological conditions and individual work attitudes is still very little. Through empirical investigations on 120 managers in a manufacturing company in Indonesia, this study found that psychological ownership was positively related to entrepreneurial behavior and job satisfaction to managers. Further research found that job satisfaction is positively related to entrepreneurial behavior and mediates the relationship between psychological ownership and entrepreneurial behavior. This study contributes to the literature by showing the relationship between psychological ownership and pro-organizational behavior, extending psychological ownership research to the field of corporate entrepreneurship through managerial entrepreneurial behavior.